2013
DOI: 10.1177/1559827613498059
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Physical Activity Interventions

Abstract: This article provides a comprehensive review of Internet– and Website–based physical activity interventions targeting adult populations. Search procedures identified 72 unique Internet-based physical activity interventions published in peer-reviewed journals. Participants of the studies were predominately White, middle-aged (mean age = 43.3 years), and female (65.9%). Intervention durations ranged from 2 weeks to 13 months (median = 12 weeks). Forty-six of the studies were randomized controlled trials, 21 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 88 publications
(198 reference statements)
6
127
1
Order By: Relevance
“…Although there is a consistent body of research demonstrating that individualised physical activity and exercise interventions lead to increased adherence, the results of Ström et al (2013) suggest that a standardised online physical activity intervention can lead to positive results, in line with the findings of the Joseph et al review of internetbased physical activity interventions in the general population (Joseph et al, 2014). Further research is needed to examine and compare the impact of individualised versus tailored approaches, as well as selfguided versus clinician-guided online interventions for physical activity on symptom severity and adherence rates.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Although there is a consistent body of research demonstrating that individualised physical activity and exercise interventions lead to increased adherence, the results of Ström et al (2013) suggest that a standardised online physical activity intervention can lead to positive results, in line with the findings of the Joseph et al review of internetbased physical activity interventions in the general population (Joseph et al, 2014). Further research is needed to examine and compare the impact of individualised versus tailored approaches, as well as selfguided versus clinician-guided online interventions for physical activity on symptom severity and adherence rates.…”
Section: Discussionsupporting
confidence: 52%
“…There has been extensive research in this area in the general adult population. Supporting the results of an earlier meta-analysis (Davies et al, 2012), a recent systematic review of 46 randomised controlled trials (RCTs) of internetdelivered physical activity interventions found that internet-based interventions were effective in increasing physical activity (Joseph et al, 2014). However, the question as to whether online physical activity interventions are effective for people with mental disorders has not yet been systematically reviewed or evaluated.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 93%
“…Although these studies were limited by short follow-up times (range 2–52 weeks, median 12 weeks) and publication bias, a small but significant effect was noted at 6 months 54. A subsequent review included non-randomised and randomised-controlled trials, experimental studies lacking control groups, and single-group observational studies 55. The intervention duration ranged from 2 weeks to 13 months (median 12 weeks).…”
Section: Prevention Initiativesmentioning
confidence: 99%
“…Forty-four of the 72 studies (61.1%) reviewed reported significant increases in PA after the intervention. However, only 6 of the 16 studies (37.5%) that included extended post-intervention follow-up demonstrated increased PA levels that were maintained 55. Additional studies are needed to clarify the effectiveness of these interventions.…”
Section: Prevention Initiativesmentioning
confidence: 99%
“…Internet-based interventions for promoting physical activity can help to overcome many of the barriers of face-to-face interventions, have the potential to reach a large segment of the population at a relatively low cost, and have been widely used for promoting physical activity in predominantely non-Hispanic White populations. 3 However, few published interventions have harnessed technology-based approaches to promote PA in minority populations, 3 despite the need and likely appeal.…”
Section: Introductionmentioning
confidence: 99%